A cyclic lipodepsipeptide, a spirolactone, and a chromanone from the marine fungus Verruculina enalia (Kohlm.) Kohlm. & Volkm.-Kohlm. BCC 22226. Issue 41 (9th October 2020) - Bunyapaiboonsri, Taridaporn; Yoiprommarat, Seangaroon; Suntivich, Rinrada; Preedanon, Sita; Komwijit, Somjit; Teerawatananond, Thapong; Sakayaroj, Jariya
Abstract: A cyclic lipodepsipeptide, verruculin, a rosigenin and an aposphaerin analogues, verruculinone and 7- O -methylaposphaerin C, together with six known compounds were isolated from the marine fungus Verruculina enalia BCC 22226. The structures of these compounds were elucidated by extensive spectroscopic analysis. The absolute configuration of verruculin was determined by Marfey's method, and the relative configuration of verruculinone was obtained by X-ray crystallography. Verruculin showed weak antituberculosis and antibacterial activities, while verruculinone displayed cytotoxicity against cancer cell (MCF-7 and NCI–H187) and Vero cell lines. Graphical abstract: Image 1 Highlights: A cyclic lipodepsipeptide and a spirolactone were isolated from the fungus V. enalia. The absolute configuration of 1 was determined by Marfey's method. The relative configuration of 2 was obtained by X-ray crystallography. Compound 1 showed weak antituberculosis and antibacterial activities. Compound 2 displayed cytotoxicity against cancer cell and Vero cell lines.